Pengaruh Kualitas Pelayanan dan Kepuasan terhadap Loyalitas Pendengar RRI Pro 1 Fm 91.2 Mhz Jakarta - Ida Nur Aprilia; Ety Nurhayaty (STIKes Ibnu Sina Ajibarang, 2024)
In the era of increasingly strict media digitalisation, it encourages the birth of various new media, especially those related to advances in the information technology sector which provide alternative access. Service quality is very important for companies, with the quality of service provided can affect satisfaction and will have an impact on long-term loyalty to RRI PRO 1 Jakarta listeners. The purpose of this study was to determine the effect of service quality and satisfaction on the loyalty of RRI PRO 1 Jakarta listeners. The analysis method in this study uses several test stages ranging from validity test, reliability test, normality test, multicolinerity test, heteroscedasticity test, linearity test, multiple linear regression, t test, f test, determination test. The sampling method in this study was purposive sampling technique. The results showed that the service quality variable had a positive and significant effect on listener loyalty with a value of 0.028> 0.05, while the satisfaction variable had a significant effect on loyalty with a value of 0.012> 0.05 while in the simultaneous hypothesis test, service quality and satisfaction had a positive effect on the loyalty of RRI PRO 1 Jakarta listeners obtained an F value of 7.535.